Spinoza : basic concepts - Campos, Andre Santos, 1980- (Exeter, UK : IA, Imprint-Academic.com, 2015)
Spinoza is among the most pivotal thinkers in the history of philosophy. He has had a deep and enduring influence on a wide range of philosophical subjects, and his work is encountered by all serious students of Western philosophy. His Ethics is one of the seminal works of metaphysical, moral, religious and political thought; his Theological-Political Treatise inaugurated a novel method of biblical exegesis; and both his political works developed the pre-eminence of democracy above all other regimes. Nevertheless, the significance of Spinoza's philosophy is matched by its complexity. His syste.
The State: Spinoza's Institutional Turn, Sandra FieldDemocracy, Martin Saar; Language, Biblical Interpretation, and Philosophy, Guadalupe González Diéguez; Back matter; Bibliography; About the Contributors; Also available.
eBooks on EBSCOhost
Keywords: Spinoza, Benedictus de, -- 1632-1677.; Spinoza, Benedictus de, -- 1632-1677; PHILOSOPHY -- History & Surveys -- Modern